Implementation of deep learning approach in equivalency education at PKBM Al Insan - Nurul Haifa; Elih Sudiapermana; Nike Kamarubiani; Sodikin Sodikin; Cucu Sukmana (Universitas Pendidikan Indonesia, 2025)
Equivalency education serves as a crucial alternative for providing learning opportunities to individuals excluded from formal schooling, particularly adults with diverse backgrounds and learning needs. However, learning practices in PKBM (Community Learning Centers) often remain instructional and fail to address the demand for contextual and meaningful education. This study aims to examine the implementation of a deep learning approach in the planning, implementation, and evaluation stages of the learning process within the Paket C Equivalency Program at PKBM Al Insan, Sumedang. Employing a descriptive qualitative method, data were collected through Focus Group Discussions (FGDs), observations, and in-depth interviews. Thematic analysis was employed to identify key patterns related to the study’s focus. The findings suggest that learning practices are beginning to reflect the principles of mindful, meaningful, and joyful learning, although they have not yet been systematically applied. Flexibility in scheduling and close tutor-learner relationships emerged as major strengths, while key challenges included limited theoretical understanding among tutors and the absence of structured evaluation tools. The study recommends enhancing tutor capacity and developing contextual learning instruments to support better the application of the deep learning approach in non-formal equivalency education. Abstrak Pendidikan kesetaraan menjadi alternatif penting dalam menyediakan layanan pendidikan bagi kelompok masyarakat yang tidak terjangkau pendidikan formal, termasuk orang dewasa dengan latar belakang dan kebutuhan belajar yang beragam. Namun, praktik pembelajaran di PKBM seringkali masih bersifat instruksional dan belum sepenuhnya menjawab kebutuhan pembelajaran yang bermakna dan kontekstual. Penelitian ini bertujuan untuk mengkaji implementasi pendekatan deep learning dalam proses perencanaan, pelaksanaan, dan evaluasi pembelajaran pada Program Pendidikan Kesetaraan Paket C di PKBM Al Insan, Sumedang. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan teknik pengumpulan data melalui Focus Group Discussion (FGD), observasi, dan wawancara mendalam. Data dianalisis menggunakan pendekatan tematik untuk mengidentifikasi pola temuan sesuai fokus penelitian. Hasil menunjukkan bahwa praktik pembelajaran telah mengarah pada prinsip mindful, meaningful, dan joyful learning, meskipun belum diterapkan secara sistematis. Fleksibilitas waktu dan hubungan personal antara tutor dan peserta menjadi kekuatan utama, sementara kendala muncul pada aspek pemahaman teoritik tutor dan keterbatasan perangkat evaluasi. Studi ini merekomendasikan penguatan kapasitas tutor dan pengembangan perangkat ajar kontekstual sebagai upaya mengoptimalkan pendekatan deep learning dalam pendidikan kesetaraan. Kata Kunci: deep learning; PKBM; pendidikan kesetaraan